PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT BANK MANDIRI CABANG BATAM - Tarigan, Ria Ema Sita Br; Purba, Daris (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of facilities, service quality on customer satisfaction at Bank Mandiri, Batam City Branch. The type of research used is descriptive verification, namely by describing and explaining the variables studied and then drawing conclusions. The research objects that are independent variables are facilities (X1), service quality (X2) and customer satisfaction (Y)   as the dependent variable. The population of this research is all customers who make transactions in the January-June 2023 period, namely 1,126 customers. The sampling method used was accidental sampling, namely the technique of determining a sample based on chance by using the slovin formula so that the sample in this study totaled 92 people. The results showed the effect of facilities, service quality on customer satisfaction at the Batam branch of Bank Mandiri.   R Square 40.6%. From these results it can be concluded that the variables Facility (X1), Service Quality (X2) simultaneously affect the Customer Satisfaction variable (Y) while 59.4% are influenced by other variables not examined in this study